2021
DOI: 10.3389/frvir.2021.645153
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Virtual Reality Skill Training Applications

Abstract: This study aimed to discuss the research efforts in developing virtual reality (VR) technology for different training applications. To begin with, we describe how VR training experiences are typically created and delivered using the current software and hardware. We then discuss the challenges and solutions of applying VR training to different application domains, such as first responder training, medical training, military training, workforce training, and education. Furthermore, we discuss the common assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(104 citation statements)
references
References 140 publications
2
97
0
5
Order By: Relevance
“…In brief, breaks were classified in line with the descriptions, including break in time, which is defined as going to the shopping chart after 5 min; break in choice, which is described as buying two products instead of just one; and break in social rules, which is defined as going into a specific place and asking the examiner what to buy. Moreover, in case of partial task failures, the specific items are classified into divided attention (occurs when mental focus is directed toward multiple ideas, or tasks, at once), selfcorrection (occurs when Self-Administered Behavioral Skills-Based At-Home is directed toward tasks), and preservation (occurs when educating people around the world by creating and hosting virtual reality content to preserve historical sites) (36).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In brief, breaks were classified in line with the descriptions, including break in time, which is defined as going to the shopping chart after 5 min; break in choice, which is described as buying two products instead of just one; and break in social rules, which is defined as going into a specific place and asking the examiner what to buy. Moreover, in case of partial task failures, the specific items are classified into divided attention (occurs when mental focus is directed toward multiple ideas, or tasks, at once), selfcorrection (occurs when Self-Administered Behavioral Skills-Based At-Home is directed toward tasks), and preservation (occurs when educating people around the world by creating and hosting virtual reality content to preserve historical sites) (36).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Within the context of our study, we regard such an environment as a participatory lab simulation. In a latest review study, Xie et al (2021) provided abundant examples about VR-based training studies and practices from the sectors of first responding, medical and military practices, transportation and workforce, as well as interpersonal skills training. This review introduced main technologies used in and the overview of those trainings in different domains, and found that such works "often use a simulator that is either controlled by a real instructor or driven by a set of training tasks to improve the trainee's performance on certain tasks or skills" (Xie et al, 2021, p. 2).…”
Section: Virtual Reality and Learningmentioning
confidence: 99%
“…Within the context of our study, we regard such an environment as a participatory lab simulation. In a latest review study, Xie et al. (2021) provided abundant examples about VR-based training studies and practices from the sectors of first responding, medical and military practices, transportation and workforce, as well as interpersonal skills training.…”
Section: Virtual Reality and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, VR has been a useful tool for providing efficient education and learning methods. Real-world training has a number of limitations, such as time consuming for setting up the site and traveling to the site, the high cost of hiring a trainer, and the gap between the training content and the actual training site, whereas VR-based training can reduce the cost of training while increasing the number of training scenarios and allow trainees to experience a virtual place related to the training content while learning in the comfort of their personal site (Xie et al, 2021). In terms of the cost and site, home training videos and websites are also useful for self-training or rehabilitation (Moore et al, 2009;Lai et al, 2016;Palazzo et al, 2016), but the advantages of VR technology, such as being able to access simulated human bodies in a safe, ethical, and repetitive way, producing objective measures of performance, and allowing real-time feedback to trainees cannot be utilized in these ways.…”
Section: Introductionmentioning
confidence: 99%